Geo-Economics, Geopolitics and the Origins of India–US Semiconductor Alliance - RAJIV KUMAR (The Journal of Indian and Asian Studies)
The world is witnessing a new technological order as major powers restructure their national strategies to dominate the supply chains of semiconductors, which have emerged as the most critical technology in the post-COVID era. In this context, the origins of the India-US semiconductor alliance represent a significant development. This paper explores the drivers and defining characteristics of this partnership. By combining geo-economic and geopolitical perspectives, the paper explains India's emerging semiconductor strategies and the rationale behind the India-US semiconductor collaboration. Geo-economic factors—such as India's recognition of economic security risks during the pandemic-induced chip shortages, the crucial role of semiconductors in India's future economic growth, and its ambitions to become a chip exporter—have driven the formation of India’s new semiconductor strategy and its quest to strengthen ties with the US. Geopolitical factors, including India's heightened threat perception regarding its dependence on chip imports from China and concerns about China's technological advancements, have further bolstered this technological partnership. The India-US semiconductor alliance in the post-COVID era is defined by three major characteristics: first, unprecedented high-level political commitment to building chip partnerships; second, significant enhancement of chip-related agreements and institutional collaborations between the two countries; and third, the promotion of US semiconductor companies' presence in India. The paper also examines the future prospects of this alliance, emphasizing the substantial convergence between India and the US in the semiconductor sector and identifying key challenges that will shape the future trajectory of this partnership.